Infaunal bivalves exhibit resilience to ocean acidification but remain sensitive to food supply - Antivero, Montserrat; Caballero, Paz; Leppes, Nicolás; Lardies, Marco A. (Frontiers in Marine Science, 2025)
Soft-sediment habitats are crucial for marine coastal ecosystems, supporting diverse biodiversity both above and below the sediment. Ocean acidification, driven by rising CO2 and nutrient influx, enhances heterotrophic metabolism, raising CO2 levels and lowering pH. These alterations complicate the dynamics of tidal flat, emphasizing the need for further research into their impact on biodiversity. Within these ecosystems, deposit- and suspension-feeding bivalves play crucial roles. Tagelus dombeii, a bivalve mollusc found in soft sediments, exhibits burrowing behavior linked to food supply and is of significant commercial value in southern Chile. This study assessed the response capacity of T. dombeii to key stressors associated with global ocean change, such as ocean acidification and food availability. Our results revealed significant differences in pH levels between the water column and pore water from the sediment in experimental mesocosms. T. dombeii was affected by ocean acidification and food availability in terms of its morphological traits (i.e. length, width, height and growth rate), while oxygen consumption was influenced only by the interaction between acidification and food supply. Notably, heart rate remained constant but increased when food supply was low. Our study suggests that T. dombeii exhibits partial tolerance to variations in seawater pH and carbonate chemistry, possibly due to its natural exposure to acidic pore water, but it is sensitive to food availability. These plastic physiological responses suggest that T. dombeii may be less vulnerable to future global change scenarios, demonstrating potential resilience and ecological success in its natural habitat.